2020
DOI: 10.22541/au.159423110.06430562
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and safety of dupilumab for moderate-to-severe atopic dermatitis: a systematic review for the EAACI Biologicals Guidelines

Abstract: This systematic review evaluates the efficacy, safety and economic impact of dupilumabcompared to standard of care for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
(104 reference statements)
1
15
0
Order By: Relevance
“…The costs after the initiation of biological therapy increased in the studies that reported it derived from an increase in DC, similar to data from other chronic inflammatory diseases [41][42][43]. Despite this findings, the information collected in our review doesn't allow us to analyze the cost-effectiveness of these therapies on JIA due to the lack of information on IC (including healthrelated quality of life) before and after start of biologics and the relatively short follow-up in most of the studies.…”
Section: Discussionsupporting
confidence: 76%
“…The costs after the initiation of biological therapy increased in the studies that reported it derived from an increase in DC, similar to data from other chronic inflammatory diseases [41][42][43]. Despite this findings, the information collected in our review doesn't allow us to analyze the cost-effectiveness of these therapies on JIA due to the lack of information on IC (including healthrelated quality of life) before and after start of biologics and the relatively short follow-up in most of the studies.…”
Section: Discussionsupporting
confidence: 76%
“…Nonetheless, while there is sufficient evidence at hand and in the literature that systemic treatment with dupilumab is highly effective in treating nasal polyps – particularly in patients with Samter triad – we believe that ASA desensitization – in low doses – may have its place in multimodal treatment of Samter triad. Firstly, there are considerable costs [ 21 , 22 ] that are associated with long term dupilumab therapy. Moreover, ASA desensitization allows the administration of oral NSAID.…”
Section: Discussionmentioning
confidence: 99%
“…102 A recent systematic review showed that anti-IL-4 and IL-13 receptor monoclonal antibodies (dupilumab), anti-IL-5 monoclonal antibodies (mepolizumab and reslizumab), and anti-IL-5 receptor alpha monoclonal antibodies (benralizumab) are effective treatments for severe asthma and AD. [103][104][105][106][107][108][109] Type 2 cytokines can cause barrier dysfunction by downregulating filaggrin gene expression. Mitamura et al reported that IL-24, a member of the IL-20 family, mediates the IL-13-induced downregulation of filaggrin gene expression.…”
Section: Cytokines and Hormonal Factorsmentioning
confidence: 99%
“…On the other hand, Sweerus et al reported that IL‐13 downregulates the expression of claudin‐18 but not of claudin‐1, ‐4, and ‐7 102 . A recent systematic review showed that anti–IL‐4 and IL‐13 receptor monoclonal antibodies (dupilumab), anti–IL‐5 monoclonal antibodies (mepolizumab and reslizumab), and anti–IL‐5 receptor alpha monoclonal antibodies (benralizumab) are effective treatments for severe asthma and AD 103‐109 . Type 2 cytokines can cause barrier dysfunction by downregulating filaggrin gene expression.…”
Section: Microbiota Changesmentioning
confidence: 99%